Čin a ne riječi ili što ih još vrag nije odnio (Dubrovačka trilogija, imperativ prošlosti i Vojnovićevo kategoričko Ne) - Rafolt, Leo (Array, 2002)
In this article author argues the problem of conservative ideologies fully present in Vojnović's dramatic triology, especially regarding issues like history, myth, concepts of modernism etc.